2000
DOI: 10.1080/03069880050013520
|View full text |Cite
|
Sign up to set email alerts
|

Counselling in primary care: A review of the practice evidence

Abstract: This paper describes the level of mental health problems that are encountered in primary health care. The limitations of using randomised control trials (RCTs) in evaluating effectiveness of psychological therapies in primary health care are described. Although the RCT may be useful in evaluating interventions in highly controlled situations, its use in evaluating clinically representative service delivery research is limited. A three-stage model of psychological therapies research is described to show that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 22 publications
2
22
1
Order By: Relevance
“…Recent studies comparing cognitive behaviour therapy with counselling in primary care showed no significant differences in outcomes 16. Such results show the dangers of tying government policies too closely to specific research findings.…”
Section: Cognitive Behaviour Therapy In Primary Carementioning
confidence: 82%
“…Recent studies comparing cognitive behaviour therapy with counselling in primary care showed no significant differences in outcomes 16. Such results show the dangers of tying government policies too closely to specific research findings.…”
Section: Cognitive Behaviour Therapy In Primary Carementioning
confidence: 82%
“…To date ve systematic research reviews, citing a plethora of research papers, have attempted to assess the ef cacy of counselling in primary care for a range of common mental health disorders (Friedli and King 1996;Godber 1996;Hemmings 2000;Roth and Fonagy 1996;Rowland et al 2000). The rst three publications that appeared in 1996 presented a consensus that there was no research evidence to suggest that counselling was either clinically or cost-effective despite its popularity with general practitioners and patients.…”
Section: Research Reviews Of Counselling In Primary Health Carementioning
confidence: 99%
“…Research on unhelpful interactions in counselling is considerably less extensive than it is for helpful factors, possibly because clients are, on the whole, very positive about their counselling (Bowman & Fine, 2000;Hemmings, 2000;Seligman, 1995). Other reasons include the possibility that clients are reluctant to criticise their counsellors (Farber, 2003;Hill et al, 1993) and are tolerant of a less-thanperfect performance by their counsellor (Farber, 2003;Hill et al, 1993;Rennie, 1994).…”
Section: (10) Clients Are Aware Also Of the Unhelpful Things Their Comentioning
confidence: 93%
“…Given the substantial gap that exists between those who need mental health services, including counselling, and those who actually seek such services (Alvidrez, 1999;Bayer & Peay, 1997;Bridgman, 1994;Clarkin & Levy, 2004;Hemmings, 2000;Vessey & Howard, 1993), there is a need to better understand the help-seeking behaviour of counselling clients. Previous research has found that most clients follow a similar process in seeking counselling, one that tends to fit with Saunders' (1993) four step model of help-seeking.…”
Section: Part 1: the Process Of Seeking Counsellingmentioning
confidence: 98%